Chapter 8 - Lentil genome sequencing: Establishing a comprehensive platform for molecular breeding - Baum, Michael; Kumar, Jitendra (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2024)
Lentil (Lens culinaris Medik.) is an important cool season food legume crop. It has a large and complex genome. Sequencing of the genome is important to enrich lentil crops with genomic resources for molecular breeding. During past years considerable attention has been given to the sequencing of the lentil genome, which has led to the development of expressed sequence tags (ESTs), unigenes, transcripts, and sequences. Efforts have also been made to develop a whole genome sequence of lentils and a draft genome sequence of 3.69 Gb was developed as a reference genome for the future. These genome sequencing efforts have provided a comprehensive platform for molecular breeding in lentils. This chapter discusses the prospects of the lentil genome sequencing platform for revolutionizing genomic research and its use in genomic-assisted breeding in lentils.